2008
DOI: 10.1371/journal.pbio.0060232
|View full text |Cite
|
Sign up to set email alerts
|

Interconvertible Lac Repressor–DNA Loops Revealed by Single-Molecule Experiments

Abstract: At many promoters, transcription is regulated by simultaneous binding of a protein to multiple sites on DNA, but the structures and dynamics of such transcription factor-mediated DNA loops are poorly understood. We directly examined in vitro loop formation mediated by Escherichia coli lactose repressor using single-molecule structural and kinetics methods. Small (∼150 bp) loops form quickly and stably, even with out-of-phase operator spacings. Unexpectedly, repeated spontaneous transitions between two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
123
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(139 citation statements)
references
References 79 publications
16
123
0
Order By: Relevance
“…For example, AFM does not have enough resolution to decipher the details of repressor binding to DNA. However, it permits visualization of the loop shape and protein position within the loop (15). Similarly, LacI was deduced to mediate A1 loops on a negatively supercoiled plasmid with 197 bp interoperator distance (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AFM does not have enough resolution to decipher the details of repressor binding to DNA. However, it permits visualization of the loop shape and protein position within the loop (15). Similarly, LacI was deduced to mediate A1 loops on a negatively supercoiled plasmid with 197 bp interoperator distance (16).…”
mentioning
confidence: 99%
“…Therefore, a further refinement of the role of various loops can be accomplished only by using an ensemble averaging free single-molecule approach, which enables dynamic observation of loop formation/breakdown and, therefore, offers the potential to identify diverse and temporally separate species, as demonstrated in the work by Finzi and Gelles using tethered particle motion (TPM) (21). A subsequent experiment on a DNA construct with shorter (158 bp and 153 bp) inter-operator spacings led to the observation of two interconverting looped states, attributed to a V-shape and an open tetramer conformer (15).…”
mentioning
confidence: 99%
“…The LacI particles could be catalogued as either in the closed or open conformations22, 23 that were especially clear in DNA molecules with LacI‐mediated loops [Fig. 1(B)].…”
Section: Resultsmentioning
confidence: 99%
“…This early study also indicated that the primary mechanism for loop breakdown was not tetramer dissociation into two bound dimers, but tetramer dissociation from operator DNA (7). Further TPM experimentation (11,29) accompanied by AFM imaging (30) showed that the loop is preferentially antiparallel and that LacI may adopt two structures in dynamic equilibrium: the "V" conformation observed in crystallographic studies and a more extended conformation that considerably relieves the strain due to DNA bending. Protein flexure may facilitate the ability to switch between different structures in simple short loops.…”
Section: Specific Dna Looping and Flexibility Of The Closure Proteinmentioning
confidence: 99%